2018
DOI: 10.1080/03054985.2018.1502079
|View full text |Cite
|
Sign up to set email alerts
|

Exploring practicum: student teachers’ social capital relations in schools with high numbers of pupils living in poverty

Abstract: The complexity of practicum in Initial Teacher Education, in terms of the range of diverse social relations and differing school contexts, provides a challenge for teacher educators worldwide, aiming to guide and shape opportunities for student teachers learning to teach. This challenge is further compounded by societal problems linked to child poverty. Drawing from social capital theory, this paper explores the kinds of social relations that are currently associated with student teachers' practicum experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The results of the study also revealed a crucial need for better preparation in supporting the professional learning of student teachers (Graham et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The results of the study also revealed a crucial need for better preparation in supporting the professional learning of student teachers (Graham et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…Nine semi-structured individual interviews were conducted with the mathematics teacher participants. Interviews are a tool used by researchers to better understand the facts of and gain knowledge about the phenomenon being studied (Graham et al, 2019). According to Creswell (2012), semi-structured interviews are useful in small-scale educational research, such as this research study, due to the flexibility of the method.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes some of the themes mentioned in the introduction, gender, disability, child carers and new arrival children, and the issues of the social and cultural capital that underpin initiatives such as the mentoring programme and the Caledonian Club. There are innovative new research findings that are emerging from the University of Aberdeen about the challenges for student teachers in engaging with children from backgrounds of poverty and deprivation (Graham et. al.…”
Section: Discussionmentioning
confidence: 99%